Analisis dan Pemetaan Pengaruh Kecepatan Kendaraan terhadap Tingkat Kebisingan di Kawasan Sekolah Dasar Kota Kendari, Sulawesi Tenggara - Herdin, Herdin; Sumarlin, Sumarlin; Ilham, Ilham; Wibowo, Dwiprayogo (Jurnal Sains dan Teknologi Lingkungan, 2024)
Noise is a sound wave generated from a vibrating sound source that causes discomfort to the listener and has an effect on health. Traffic activity is one of the sources of noise and disturbs the comfort of school children. Therefore, this study aims to analyze the noise potential in elementary schools (SD) on the edge of the Kendari City primary road mathematically, then map the results of noise calculations. The sampling technique was carried out by calculating the volume of traffic vehicles such as motorcycles, light vehicles, and heavy vehicles. Measurements were carried out on Monday-Friday at each point one day, the measurement time was at 08.00 - 09.00 WITA. Travel time is done by recording the time required to pass the road segment. Based on these results that the Predicted Noise Level (PNL) calculation, the highest potential noise level is at SDN 7 Kendari at 67.09 dB(A), SDN 37 Kendari at 66.53 dB(A), SDN 6 Kendari at 65, 05 dB(A), SDN 2 Kendari is 64.84 dB(A), SDN 30 Kendari is 64.53 dB(A), and SDN 28 Kendari is 62.48 dB(A). The presentation of data in the form of spatial/map data is very important because of the large number of research locations, with the presentation of the data in the form of a map, making it easier for researchers to analyze the noise potential by making points, so that they become reference materials for the great potential of PNL in Kendari City.